Temporal changes in mouse hippocampus transcriptome after pilocarpine-induced seizures - Popova, Evgenya Y.; Kawasawa, Yuka Imamura; Leung, Ming; Barnstable, Colin J. (Frontiers in Neuroscience, 2024)
Introduction Status epilepticus (SE) is a seizure lasting more than 5 min that can have lethal consequences or lead to various neurological disorders, including epilepsy. Using a pilocarpine-induced SE model in mice we investigated temporal changes in the hippocampal transcriptome. Methods We performed mRNA-seq and microRNA-seq analyses at various times after drug treatment. Results At 1 h after the start of seizures, hippocampal cells upregulated transcription of immediate early genes and genes involved in the IGF-1, ERK/MAPK and RNA-PolII/transcription pathways. At 8 h, we observed changes in the expression of genes associated with oxidative stress, overall transcription downregulation, particularly for genes related to mitochondrial structure and function, initiation of a stress response through regulation of ribosome and translation/EIF2 signaling, and upregulation of an inflammatory response. During the middle of the latent period, 36 h, we identified upregulation of membrane components, cholesterol synthesis enzymes, channels, and extracellular matrix (ECM), as well as an increased inflammatory response. At the end of the latent period, 120 h, most changes in expression were in genes involved in ion transport, membrane channels, and synapses. Notably, we also elucidated the involvement of novel pathways, such as cholesterol biosynthesis pathways, iron/BMP/ferroptosis pathways, and circadian rhythms signaling in SE and epileptogenesis. Discussion These temporal changes in metabolic reactions indicate an immediate response to injury followed by recovery and regeneration. CREB was identified as the main upstream regulator. Overall, our data provide new insights into molecular functions and cellular processes involved at different stages of seizures and offer potential avenues for effective therapeutic strategies.